2009
DOI: 10.1038/ng.347
|View full text |Cite
|
Sign up to set email alerts
|

A common variant on chromosome 11q13 is associated with atopic dermatitis

Abstract: We conducted a genome-wide association study in 939 individuals with atopic dermatitis and 975 controls as well as 270 complete nuclear families with two affected siblings. SNPs consistently associated with atopic dermatitis in both discovery sets were then investigated in two additional independent replication sets totalling 2,637 cases and 3,957 controls. Highly significant association was found with allele A of rs7927894 on chromosome 11q13.5, located 38 kb downstream of C11orf30 (P(combined) = 7.6 x 10(-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
271
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 292 publications
(297 citation statements)
references
References 27 publications
14
271
0
12
Order By: Relevance
“…29 A GWA study for atopic dermatitis identified an SNP (rs7927894) on chromosome 11q13.5 with increased risk for developing atopic dermatitis of 1.47 for AA homozygotes. 22 A well-established atopic dermatitis gene FLG 35 was not found to be a 'top' significant signal, but was in close linkage with a significantly associated region located 156 kb away. 22 Himes et al 36 conducted a GWA study on 359 cases from the Childhood Asthma Management Program (CAMP) and 846 genetically matched controls, and also sought the replications in 10 independent populations.…”
Section: Findings In Several Gwa Studies On Asthmamentioning
confidence: 94%
See 2 more Smart Citations
“…29 A GWA study for atopic dermatitis identified an SNP (rs7927894) on chromosome 11q13.5 with increased risk for developing atopic dermatitis of 1.47 for AA homozygotes. 22 A well-established atopic dermatitis gene FLG 35 was not found to be a 'top' significant signal, but was in close linkage with a significantly associated region located 156 kb away. 22 Himes et al 36 conducted a GWA study on 359 cases from the Childhood Asthma Management Program (CAMP) and 846 genetically matched controls, and also sought the replications in 10 independent populations.…”
Section: Findings In Several Gwa Studies On Asthmamentioning
confidence: 94%
“…22 A well-established atopic dermatitis gene FLG 35 was not found to be a 'top' significant signal, but was in close linkage with a significantly associated region located 156 kb away. 22 Himes et al 36 conducted a GWA study on 359 cases from the Childhood Asthma Management Program (CAMP) and 846 genetically matched controls, and also sought the replications in 10 independent populations. In seven white and Hispanic replication populations, two PDE4D SNPs had significant results with P-values less than 0.05, and five had results in the same direction as the original population but had P-values greater than 0.05.…”
Section: Findings In Several Gwa Studies On Asthmamentioning
confidence: 94%
See 1 more Smart Citation
“…Most other candidate genes for AD show inconsistent replication patterns. Data on the recently identified AD susceptibility gene from chromosome 11 identified by a GWA study [35] has not yet been replicated sufficiently to judge its relevance and robustness.…”
Section: Clinical Impact Of Genetic Findingsmentioning
confidence: 99%
“…This GWA study incorporated more than 307,000 SNP markers and 10,000 individuals from both family and case-referent panels mainly collected from Germany [35]. A robust site of association was identified on chromosome 11q13.5, with the strongest association observed for SNP rs7927894, which is located in an intergenic region between two annotated genes, chromosome 11 open reading frame 30 (C11orf30) and leucine rich repeat containing 32 (LRRC32) [UCSC Genome Browser, Human Genome March 2006 assembly, 259 http://genome.ucsc.edu].…”
Section: Hints From Genomewide Studiesmentioning
confidence: 99%